Alasdair Allan on making use of iPhone and iPad location sensors - Allan, Alasdair ([O'Reilly Media], 2010)
"This video guides you through developing applications for the iPhone and iPad platforms that make use of the onboard sensors: the three-axis accelerometer, the magnetometer (digital compass), the gyroscope, the camera and the global positioning system. You'll learn how to make use of these onboard sensors and combine them to build augmented reality applications. This will give you the background to building your own applications independently using the hottest location-aware technology yet for any mobile platforms"--Resource description page.
Keywords: iPhone (Smartphone); iPad (Computer); Apple computer -- Programming; iPhone (Téléphone intelligent); iPad (Ordinateur); Apple computer; Programming; Electronic videos